RADIOATIVIDADE: uma proposta para a aprendizagem significativa para o ensino de química. - CLAUDEMAR FREDERICE (2023)
In recent years, basic education has undergone a great change. The Common National Curriculum Base aims to give students a life project so that they develop ethical and political principles, always working on the socio-emotional side for integral human development, resulting in student protagonism. The Chemistry discipline requires special attention, because besides theory, practice must be prioritized, because it is at this moment that the student is encouraged to use his imagination in the search for an explanation of the phenomenon that is happening. Besides drawing attention, the practice must be in accordance with the objectives to be achieved and thus enrich the knowledge of our students. Some contents, such as radioactivity, for example, are difficult to demonstrate experimentally due to their experimental complexity and high costs. In recent years, the Arduino platform, which consists of a board designed with a microcontroller and free software, has been proposed as a teaching tool, mainly for its low cost and easy programming. Therefore, this research project involves the development of a methodology for a theoretical and experimental lesson on Radioactivity as a significant didactic proposal for student learning for teaching in the subject of High School Chemistry. The objective is to assemble a theoretical and practical product, testing the Arduino Platform, already programmed to be used as a Geiger-Müller counter in experimental Radioactivity classes to detect radiation from Brazilian natural objects and minerals through exploratory research. The project was applied to teachers from state schools in the State Education Network of Mato Grosso do Sul - MS, in which they evaluated and validated the effectiveness of the product. The evaluation and validation were done by means of a questionnaire prepared by me, where the results of the analyzed data were given by summing the values of the answers, divided by the number of participants, where sixty to one hundred percent was considered satisfactory, forty to fifty-nine percent as unsatisfactory, with revision and change of some undesired points, and below forty percent as totally bad and the project rethought. At the end of the project, I produced a kit as low-cost didactic material with a theoretical and practical part, containing a Geiger Müller counter and objects that emit radiation to be identified in experimental radioactivity classes. Keyword: Arduino; Didactic Material; Radioactivity Experiment; Chemistry Teaching; Geiger Müller Counter.